Thermal performance and flow pattern of an immersion spray array cooling vapor chamber - Yi, Li (2023)
An immersion spray array cooling vapor chamber (ISVC) is proposed for high-power electronic devices. Experimental and numerical studies on thermal performance and flow pattern have been conducted. It is shown that increasing the inlet temperature of the coolant facilitates the heat transfer performance and temperature uniformity of the ISVC within the safe working temperature range of electronic devices. The immersed spray impingement process includes a stage of velocity reduction from the nozzle exit to the target surface, a process of velocity boundary layer formation on the target surface, and a flow collision region formation process of adjacent sprays. As the inlet flow rate increases, the effect of the spray on the target surface is enhanced and the interaction between adjacent sprays is stronger. The perturbation effect of the spray on the fluid in the impingement cavity is positively influenced by the inlet flow rate. The spray array has a strong stirring effect on the water in the spray chamber in the XY, XZ and YZ planes. The heat transfer capacity of the ISVC is enhanced with a larger inlet flow rate due to the enhanced spray effect and larger spray coverage area. The temperature uniformity of the ISVC is improved with an increase of flow rate. The ISVC operating limit heating powers of 2.0 L/min, 4.0 L/min and 7.0 L/min flow rates are 531 W, 575 W and 600 W. Compared to the existing integrated heat sink combined vapor chamber and array jet impingement, the operating limit heating power of ISVC is increased by at least 68%.